Long-lasting cardiovascular modulation in female rats induced by topiramate administration during pre-adolescence - Silva, Kenny Gutemberg Nunes; Miguel, Maria Vitória Oliveira; Bonancea, Amanda Monteiro; de Oliveira, Gabriella Rossato; da Silva, Deborah Gomes; Vidigal, Camila Borecki; Moura, Kawane Fabricio; Andrade, Karoliny Coelho; Ceravolo, Graziela Scalianti; Martins-Pinge, Marli C; Crestani, Carlos C [UNESP]; Alves, Fernando Henrique Ferrari; et al. (Elsevier, 2025)
Studies showed that administration of topiramate (TPM) could cause cardiovascular changes, but the enduring effects of this use during early life phases are unknown. The present work evaluated whether treatment with TPM administered during pre-adolescence would cause long-term effects in adulthood on cardiovascular parameters in female rats. In this way, female Wistar rats were treated from postnatal day (PND) 16 to 28 with water or TPM (41mg/kg/day) via gavage. In adulthood, at PND85, the female rats were tested by identify the oestrus phase. Each one in the oestrus phase were subjected to cardiovascular activity assessment protocols. In the PND86, the rats were evaluated for: baseline cardiovascular parameters, baroreflex, haemodynamic and acute restraint stress reactivity. In TPM treated female rats, baroreflex assessment indicated an increase in the slope of the bradycardic response in response to mean arterial pressure increases caused by intravenous infusion of phenylephrine. Treatment with TPM also enhanced pressor response to the vasoactive drugphenylephrine. Conversely, TPM did not affect the pressor and tachycardic responses evoked by acute restraint stress. These findings demonstrated that administration of TPM during pre-adolescence modified the autonomic response of baroreflex component and altered haemodynamic response to vasoactive drugs in adulthood in female rats, suggesting a long-term effect on cardiovascular modulation.